Töprengések a területi szintű stratégiai tervezésről - Rechnitzer, János (Tér és Társadalom, 1995)
The author makes an attempt is his essay to apply the way of thinking and the methods of strategic planning in regional planning. His starting point is that the development of the regional system is formed by the common system of exogenous and endogenous factors, all of which define different pictures of the future as development possibilities. Strategic planning, which promotes a creative thinking looking into the future, is built on flexible systems, at the same time it requires the use of active methods. With its change-oriented view, striving for a lasting success, it is suitable for being a new tool of the development of the regional system. The essay compares traditional regional planning and a few factors of the strategic view planning, at the same time it draws attention to the limits of the use of this latter method. It talks about the problems of duration and it emphasises the need for thinking not in political cycles but in development periods in regional planning. On examining the exogenous and endogenous factors applied in strategic planning he raises the fears that it is problematic to put the strategies of the actors of the regional unit into a system. Also, it is difficult to find what elements of the environment really affect the regional system and where the spatial borders of that can be drawn. The uncertainty of the information concerning the future is analysed in the essay as are the weaknesses of the methods of cognition. The author talks about the factors hindering the innovationorinted view, i.e. strong external dependence, the character of the connection among the elements of the system and the lack of regional identity. He analyses in details the role of actions in strategic planning, since this is where he sees a solution for the lasting contradiction of regional development and regional planning. Finally he mentions the limits of social participation as well as the institutionalised systems of the assertion of different interests, but he is unable to solve this serious planning anomaly. In the following part of the essay we get instructions for the creation of a strategic view regional plan. The author starts the analysis of the problem by setting up a hypothetical picture of the future, then he goes on to offer aspects for the examination of exogenous and endogenous factors. In the analysis of the environment he evaluates international trends, gives an overview of the clients, the consumers of the regional system, also, he talks about the issues of studying the competitors. From the endogenous factors he mentions the endogenous resources of the regional system, the present strategies and the management and tools of regional development. The author briefly introduces the process of strategy building, emphasising the possibilities offered by the analysis of the scenarios. The final phase of planning is the definition of the elements of the accepted strategy, the objectives, priorities and programmes, also, the launch of the organisation of the future itself, an outline of the tasks of regional management. The statements of the essay can be summarised by saying that the strategic view regional planning can give us a new approach of regional development and it can contribute to its tools as well as to the sphere of action of regional policy, not to mention the renewal of the operation possibilities of regional management. In other words, ít can initiate a new way of thinking and action by the actors of the regional system.